On the economic impact of international sport events: Microevidence from survey data at the EURO 2008 - Michael J. Lamla; Martin Straub; Esther M. Girsberger Seelaus (ETH Zurich, KOF Swiss Economic Institute, 2012)
Using firm-level data for up to 707 Swiss hotels and restaurants we evaluate the economic impact of the EURO 2008 soccer championship. Although aggregated macro data reveal no economic impact, we report an overall negative effect based on the surveyed companies. Notably the reported effects of the individual firms are very heterogeneous. For instance, hotels in cities benefitted from the tournament as they were able to raise prices and thereby increase profits. Looking at the long-run impact only a small fraction of companies do believe in a positive effect. Interestingly, this outlook does not depend on earnings, but on the guest structure.
Keywords: L83; O18; R11; 330; Euro 2008; Mega-event; firm-level data; Sportveranstaltung; Fußballsport; Makroökonomischer Einfluss; Gastgewerbe; Österreich; Schweiz